Mitigation choices impact carbon budget size compatible with low temperature goals - Joeri Rogelj; Andy Reisinger; David L McCollum; Reto Knutti; Keywan Riahi; Malte Meinshausen (Environmental Research Letters, 2015)
Global-mean temperature increase is roughly proportional to cumulative emissions of carbon-dioxide (CO _2 ). Limiting global warming to any level thus implies a finite CO _2 budget. Due to geophysical uncertainties, the size of such budgets can only be expressed in probabilistic terms and is further influenced by non-CO _2 emissions. We here explore how societal choices related to energy demand and specific mitigation options influence the size of carbon budgets for meeting a given temperature objective. We find that choices that exclude specific CO _2 mitigation technologies (like Carbon Capture and Storage) result in greater costs, smaller compatible CO _2 budgets until 2050, but larger CO _2 budgets until 2100. Vice versa, choices that lead to a larger CO _2 mitigation potential result in CO _2 budgets until 2100 that are smaller but can be met at lower costs. In most cases, these budget variations can be explained by the amount of non-CO _2 mitigation that is carried out in conjunction with CO _2, and associated global carbon prices that also drive mitigation of non-CO _2 gases. Budget variations are of the order of 10% around their central value. In all cases, limiting warming to below 2 °C thus still implies that CO _2 emissions need to be reduced rapidly in the coming decades.